SÍNDROME COMPARTIMENTAL AGUDO EN EL PACIENTE QUEMADO ELÉCTRICO - Piccolo Johanning, Loretta (2011)
Acute compartment syndrome is a disease withhigh morbidity and mortality, which must betaken into account when assessing a patientsuffering from electrical burns. Early diagnosistends to reduce sequelae and improve prognosis.There is no consensus about the pressuresrequired to generate intracompartmental damage,and most of the time the diagnosis is purelyclinical. The only approved treatment isfasciotomy of the affected compartment.